Effect of off-stoichiometric composition on half-metallic character of Co2Fe(Ga, Ge) investigated using saturation magnetization and giant magnetoresistance effect. (25th August 2022) - Chikaso, Yuki; Inoue, Masaki; Tanimoto, Tessei; Kikuchi, Keita; Yamanouchi, Michihiko; Uemura, Tetsuya; Inubushi, Kazuumi; Nakada, Katsuyuki; Shinya, Hikari; Shirai, Masafumi
Abstract: We investigated the Ge-composition ( γ ) dependence of the saturation magnetization of Co2 Fe(Ga, Ge) (CFGG) thin films and the magnetoresistance (MR) ratio of CFGG-based current-perpendicular-to-plane giant magnetoresistance (CPP-GMR) devices together with first-principles calculations of the electronic states of CFGG. Theoretical calculations showed that spin polarization is highest at the stoichiometric composition γ = 0.56 in Co2 Fe1.03 Ga0.41 Ge γ and that it decreases in off-stoichiometric CFGG, mainly due to the formation of CoFe antisites for Ge-deficient compositions and FeCo antisites for Ge-rich compositions, where CoFe (FeCo ) indicates that Co (Fe) atoms replace the Fe (Co) sites. The saturation magnetic moment ( μ s ) per formula unit decreased monotonically as γ increased from 0.24 to 1.54 in Co2 Fe1.03 Ga0.41 Ge γ . The μ s was closest to the Slater–Pauling value predicted for half-metallic CFGG at the stoichiometric composition γ = 0.56, indicating that stoichiometric CFGG has a half-metallic nature. This is consistent with the result for the theoretical spin polarization. In contrast, the MR ratio of CFGG-based CPP-GMR devices increased monotonically as γ increased from 0.24 to 1.10 and reached an MR ratio of 87.9% at the Ge-rich composition γ = 1.10. Then, the MR ratio decreased rapidly as γ increased from 1.10 to 1.48. Possible origins for the slight difference between the Ge composition at which the highest MR ratio was obtained ( γ = 1.10) and that at which the highest spin polarization was obtained ( γ = 0.56) are improved atomic arrangements in a Ge-rich CFGG film and the reduction of effective Ge composition due to Ge diffusion in the GMR stacks.